Sorghum phenolic compounds associate with cell apoptosis in human hepatocarcinoma HepG2 and colorectal adenocarcinoma Caco2 cells - Shen, Jiamin (Kansas State University, 2021)
Sorghum is a rich source of various phytochemical phenolics including phenolic acids, anthocyanins, and flavonoids, etc. These phenolics have been associated with chronic disease prevention, especially cancer. However, the available data for various varieties of sorghum on cancer are limited. In this study, two different sorghum accessions were selected and the extracted phenolics were tested for their impact on cell growth and apoptosis in both hepatocarcinoma HepG2 and colorectal adenocarcinoma Caco-2 cell lines. Total phenolic contents determined by Folin-Ciocalteu were 2.11 mg GAE/g DW in F10000 and 21.89 mg GAE/g DW in PI329694, respectively. Cells treated with various concentrations of the extracted phenolics at 0-200 [mu]M GAE up to 72 hrs resulted a dose dependent reduction of cell number. The apoptosis as measured by the FITC Annexin V protocol was also resulted a significant increase in the extract of PI329694 when comparing with the extract of F10000. Overall, these results showed a positive evidence that a direct impact of the sorghum phenolics on either HepG2 or Caco-2 cellular growth inhibition and apoptosis induction. Both anti-growth and apoptotic induction seemed associated with their phenolic contents. Therefore, this study suggests that sorghum prevent against cancer through phenolic-mediated cancer cell inhibition and apoptosis induction.
Keywords: Sorghum; Phenolic compounds; Cell apoptosis; HepG2; Caco-2